Understanding and overcoming obstacles in adaptive management - Johan Månsson; Louise Eriksson; Isla Hodgson; Johan Elmberg; Nils Bunnefeld; Rebecca Hessel; Maria Johansson; Niklas Liljebäck; Lovisa Nilsson; Camilla Olsson; Tomas Pärt; Camilla Sandström; et al. (Trends in Ecology & Evolution, 2023)

Predicting intervention priorities for wildlife conflicts - Zachary Baynham‐Herd; Steve Redpath; Nils Bunnefeld; Aidan Keane (Conservation Biology, 2020)
There is growing interest in developing effective interventions to manage socially and environmentally damaging conservation conflicts. There are a variety of intervention strategies that can be applied in various contexts, but the reasons one type of intervention is chosen over another remain underexplored. We surveyed conservation researchers and practitioners ( n = 427) to explore how characteristics of conflicts and characteristics of decision makers influence recommendations to alleviate conservation conflict. Using a full‐factorial design, we experimentally manipulated 3 aspects of the descriptions of 8 different wildlife‐conflict scenarios ( development status of the conflict country, conflict framing, and legality of killing wild animals ) and recorded which of 5 intervention types ( wildlife impact reduction, awareness, enforcement, economic incentives, or stakeholder engagement ) respondents prioritized. We also recorded information on respondents’ demographic and disciplinary backgrounds. Stakeholder‐based interventions were recommended most often in the survey and in written feedback. However, when we fitted multinomial mixed logit models with fully completed scenario responses ( n = 411), recommendations were influenced by small changes in the details of conflict and differed according to respondent characteristics. Enforcement and awareness interventions were prioritized relatively more for conflicts in more highly developed nations and by respondents with more natural science backgrounds and relatively less experience with conflict. Contrastingly, economic interventions were prioritized more when wildlife killing was described as illegal. Age, gender, and development status of the respondent's home country also predicted some intervention decisions. Further, interrogating the influences shaping conservation decision making will further helps in the development of evidence‐informed interventions.

Parasites, mate attractiveness and female feather corticosterone levels in a socially monogamous bird - François Mougeot; Ádám Z. Lendvai; Jesús Martínez-Padilla; Lorenzo Pérez-Rodríguez; Mathieu Giraudeau; Fabián Casas; Ignacio T. Moore; Steve Redpath (Behavioral Ecology and Sociobiology, 2016)

The role of parasite‐driven selection in shaping landscape genomic structure in red grouse ( Lagopus lagopus scotica ) - Marius A. Wenzel; Alex Douglas; Marianne C. James; Steve M. Redpath; Stuart B. Piertney (Molecular Ecology, 2016)
Landscape genomics promises to provide novel insights into how neutral and adaptive processes shape genome‐wide variation within and among populations. However, there has been little emphasis on examining whether individual‐based phenotype–genotype relationships derived from approaches such as genome‐wide association (GWAS) manifest themselves as a population‐level signature of selection in a landscape context. The two may prove irreconcilable as individual‐level patterns become diluted by high levels of gene flow and complex phenotypic or environmental heterogeneity. We illustrate this issue with a case study that examines the role of the highly prevalent gastrointestinal nematode Trichostrongylus tenuis in shaping genomic signatures of selection in red grouse ( Lagopus lagopus scotica ). Individual‐level GWAS involving 384 SNPs has previously identified five SNPs that explain variation in T. tenuis burden. Here, we examine whether these same SNPs display population‐level relationships between T. tenuis burden and genetic structure across a small‐scale landscape of 21 sites with heterogeneous parasite pressure. Moreover, we identify adaptive SNPs showing signatures of directional selection using outlier analysis and relate population‐ and individual‐level patterns of multilocus neutral and adaptive genetic structure to T. tenuis burden. The five candidate SNPs for parasite‐driven selection were neither associated with T. tenuis burden on a population level, nor under directional selection. Similarly, there was no evidence of parasite‐driven selection in SNPs identified as candidates for directional selection. We discuss these results in the context of red grouse ecology and highlight the broader consequences for the utility of landscape genomics approaches for identifying signatures of selection.

The emergence of biodiversity conflicts from biodiversity impacts: characteristics and management strategies - Juliette C. Young; Mariella Marzano; Rehema M. White; David I. McCracken; Steve M. Redpath; David N. Carss; Christopher P. Quine; Allan D. Watt (Biodiversity and Conservation, 2010)

Bottoms up: great bustards use the sun to maximise signal efficacy - Pedro P. Olea; Fabián Casas; Steve Redpath; Javier Viñuela (Behavioral Ecology and Sociobiology, 2010)

Temporal changes in kin structure through a population cycle in a territorial bird, the red grouse Lagopus lagopus scoticus - STUART B. PIERTNEY; XAVIER LAMBIN; ANDREW D. C. MACCOLL; KERRY LOCK; PHILIP J. BACON; JOHN F. DALLAS; FIONA LECKIE; FRANCOIS MOUGEOT; PAUL A. RACEY; STEVE REDPATH; ROBERT MOSS (Molecular Ecology, 2008)
Populations of red grouse ( Lagopus lagopus scoticus ) undergo regular multiannual cycles in abundance. The ‘kinship hypothesis’ posits that such cycles are caused by changes in kin structure among territorial males producing delayed density‐dependent changes in aggressiveness, which in turn influence recruitment and regulate density. The kinship hypothesis makes several specific predictions about the levels of kinship, aggressiveness and recruitment through a population cycle: (i) kin structure will build up during the increase phase of a cycle, but break down prior to peak density; (ii) kin structure influences aggressiveness, such that there will be a negative relationship between kinship and aggressiveness over the years; (iii) as aggressiveness regulates recruitment and density, there will be a negative relationship between aggressiveness in one year and both recruitment and density in the next; (iv) as kin structure influences recruitment via an affect on aggressiveness, there will be a positive relationship between kinship in one year and recruitment the next. Here we test these predictions through the course of an 8‐year cycle in a natural population of red grouse in northeast Scotland, using microsatellite DNA markers to resolve changing patterns of kin structure, and supra‐orbital comb height of grouse as an index of aggressiveness. Both kin structure and aggressiveness were dynamic through the course of the cycle, and changing patterns were entirely consistent with the expectations of the kinship hypothesis. Results are discussed in relation to potential drivers of population regulation and implications of dynamic kin structure for population genetics.

Raptors and Red Grouse: Conservation Conflicts and Management Solutions - Simon Thirgood; Steve Redpath; Ian Newton; Peter Hudson (Conservation Biology, 2000)
Recovering predator populations may present problems for conservationists if their prey are of economic or conservation value. We address this issue by examining the conflict between raptor conservation and management of Red Grouse ( Lagopus l. scoticus ) in Britain. Heather moorland is a distinctive habitat that supports an important assemblage of breeding birds. Large areas of moorland are managed by private landowners for shooting grouse. Although grouse shooting benefits conservation by retaining heather moorland, it is currently unclear whether grouse management directly benefits other upland birds. Human persecution has greatly restricted the range and abundance of most raptor species in Britain. Following the introduction of bird protection laws, the decline in gamekeeping, and the restriction of organochlorine pesticides, raptor populations have started to recover. Persecution of raptors on grouse moors is widespread and limits the range and abundance of Hen Harriers ( Circus cyaneus ), Peregrine Falcons ( Falco peregrinus ), and Golden Eagles ( Aquila chrysaetos ). In some circumstances, raptor predation can reduce both the breeding density and productivity of Red Grouse. Limitation of grouse populations through raptor predation is most likely to occur where raptors are at high density because of the abundance of alternative prey, and grouse are at low density either because of poor management or the cyclic nature of some grouse populations. In the long term, habitat management may reduce densities of alternative prey, leading to reductions in raptor densities and their predation on grouse. More active intervention may be required, however, if grouse moors are to remain viable in the short‐term. Current research is focused on manipulating harrier diet through diversionary feeding. Complementary research is needed to investigate methods to reduce raptor numbers locally while ensuring their national status.